Cover Picture: Achieving Strong Positive Cooperativity through Activating Weak Non‐Covalent Interactions (Angew. Chem. Int. Ed. 3/2018). Issue 3 (20th December 2017) - Ma, Yan‐Long; Ke, Hua; Valkonen, Arto; Rissanen, Kari; Jiang, Wei
Abstract : Cooperativity is one of the most important underlying principles for biological systems and gregarious animals. As shown on the cover, through the cooperative efforts of a group of small ants, large objects like a leaf can be moved. This phenomenon in nature is similar to the observation reported by W. Jiang et al. in their Communication onpage 709 ff.: Strong cooperativity can be achieved through activating relatively weak non‐covalent interactions.